PSMA‐positive membranes secreted from prostate cancer cells have potency to transform vascular endothelial cells into an angiogenic state. Issue 16 (13th September 2021) - Watanabe, Ryuta; Maekawa, Masashi; Kiyoi, Takeshi; Kurata, Mie; Miura, Noriyoshi; Kikugawa, Tadahiko; Higashiyama, Shigeki; Saika, Takashi
Abstract: Background: Prostate‐specific membrane antigen (PSMA) is highly expressed in poorly differentiated, metastatic, and castration‐resistant prostate cancers. Recently, 68Ga‐PSMA positron emission tomography/computed tomography has been successfully developed as an effective diagnostic tool for prostate cancer. However, the pathophysiological functions of PSMA in prostate tumors remain unclear. Methods: We examined the protein expression of PSMA in tumor endothelial cells in human prostate tumors by immunohistochemistry. Prostate cancer tissues were resected by robotic surgery in 2019 at Ehime University from patients with prostate cancer. In vitro, we prepared conditioned medium (CM) derived from a PSMA‐positive human prostate cancer cell line, LNCaP, cultured on collagen I gels. We then examined PSMA expression in human umbilical vascular endothelial cells (HUVECs) cultured with the CM. We assessed angiogenic activities by treatment of HUVECs with LNCaP‐derived CM using a tube formation assay that mimics angiogenesis. Results: Immunohistochemistry of PSMA and CD31, a marker of endothelial cells, and PSMA‐expressing tumor endothelial cells were observed in 4 of 33 prostate cancer patients (12.1%). We also found that the 10, 000 g pellet fraction of the LNCaP‐derived CM containing PSMA‐positive membranes, such as microvesicles transformed HUVECs "PSMA‐negative" into "PSMA‐positive." Furthermore, treatment of HUVECs with the 10, 000 g pellet fraction of the LNCaP‐derived CM significantly promoted tube formation, mimicking angiogenesis in a PSMA‐dependent manner. Conclusions: Our findings revealed the existence of PSMA‐positive tumor endothelial cells in human prostate tumors, which enhances tumor angiogenesis in prostate cancer tissues.